Cholic acid resistance and the adherence ability of Bifidobacterium pseudocaenulatum G4 - Sulaiman, Ali Qahtan; Jalilian, Farid Azizi; Mustafa, Shuhaimi; Sekawi, Zamberi; Mohd Ghazali, Hasanah; Meor Hussin, Anis Shobirin; Abd Manap, Mohd Yazid (Academic Journals, 2009)
The adherence capacity of Bifidobacterium longum BB536 and Bifidobacterium pseudocatenulatum G4 on HT-29 human epithelium cell line with the presence of cholic acid were assessed. B. longum BB536 showed a higher adhesion level on HT-29 human epithelium cell line compared to B. psudocatenulatum G4. However, in the presence of physiological concentration (0.094 and 0.94 μM) of cholic acid, the adhesion level of Bifidobacterium strains dropped between 5 and 55% respectively, depending on pH, time and strain. The adaptation of Bifidobacterium strains to cholic acid was shown to be increased with time. It was concluded that the acquisition of cholic acid resistance by those Bifidobacterium strains promoted changes in the adhesion ability on HT-29 human epithelium cell line.